WO3/TiO2 composite coatings: Structural, optical and photocatalytic properties. (November 2016) - Dohčević-Mitrović, Zorana; Stojadinović, Stevan; Lozzi, Luca; Aškrabić, Sonja; Rosić, Milena; Tomić, Nataša; Paunović, Novica; Lazović, Saša; Nikolić, Marko G.; Santucci, Sandro
Graphical abstract: Highlights: WO3 /TiO2 coatings were fabricated via Plasma Electrolytic Oxidation process. With increasing time of PEO process WO3 and WO2.96 phases became dominant. Band gap red shift with increasing WO3 /WO2.96 content. Enhanced visible light photoactivity of composite coatings. Catalysts ehxibit increased adsorption affinity and charge separation efficiency. Abstract: WO3 /TiO2 and TiO2 coatings were prepared on titania substrates using facile and cost-effective plasma electrolytic oxidation process. The coatings were characterized by X-ray diffraction, scanning electron microscopy, Raman, UV–vis diffuse reflectance spectroscopy, and X-ray photoelectron spectroscopy. With increasing duration of PEO process, the monoclinic WO3 phase became dominant and new monoclinic WO2.96 phase appeared. The optical absorption edge in the WO3 /TiO2 samples, enriched with WO3 /WO2.96 phase, was shifted to the visible region. The photocatalytic efficiency of WO3 /TiO2 and pure TiO2 samples was evaluated by performing the photodegradation experiments in an aqueous solution of Rhodamine 6G and Mordant Blue 9 under the visible and UV light. The WO3 /TiO2 catalysts are much more efficient than pure TiO2 under visible light and slightly better under UV light. The improvement of photocatalytic activity in the visible region is attributed to better light absorption, higher adsorption affinity and increased charge separation efficiency.